Psoriasis: Correlation between severity index (PASI) and quality of life index (DLQI) based on the type of treatment - Ali Al Raddadi; Abdulhadi Jfri; Sahal Samarghandi; Nesreen Matury; Taha Habibullah; Majed Alfarshoti; Ahmad Mahdi (Wolters Kluwer Medknow Publications, 2016)
Background: Psoriasis vulgaris is a common chronic dermatological disease that has a negative impact on the psychological status and the social interaction of the patient. Objective: To correlate the quality of life and clinical severity of psoriasis vulgaris in patients using different types of treatment. Materials and methods: This is a prospective observational cross-sectional study that took place over a 4 month period, from January to April 2014, at the King Abdul Aziz Medical City, Jeddah, Saudi Arabia. All patients with psoriasis vulgaris attending the dermatology clinics during this period were included. Results: Of the total 41 Saudi patients, 25 were males and 16 were females. 21 were on combined (i.e. topical with either systemic or NB-UVB) and 20 were on topical treatments only. PASI score was moderate in the majority for both groups, that is, patients on topical (70%) and combined treatment (80%). DLQI score shows only a small effect on the patient's quality of life for the majority (14/20) in the topical group and (16/21) for those on combined therapy. Conclusion: There is no significant difference in terms of the effect of the type of treatment between the two groups.